Navigating the VUCA Landscape: Examining the Transformative Influence of Information Technology on Business Productivity and Performance (Universitas Terbuka, 2023)
In the rapidly advancing era of technology, the implementation of technology in the context of business administration has become a key factor in enhancing the productivity and performance of an organization. This study aims to examine how the implementation of information technology at CV Bangka Putra Persada has influenced the productivity and performance of business. This case study is crucial as it can provide concrete insights into the role of information technology in improving business administration processes at the operational level. The research utilizes a qualitative analysis method, incorporating quantitative surveys from 34 individuals and interviews with 4 staffs who have used Sales Force Automation (SFA) in administration and sales divisions. The findings reveal that the company has embraced technological advancements, namely Sales Force Assessment (SFA), to boost its revenue through increased efficiency and performance. The implementation of information technology has brought significant changes in operational processes and data administration. This is evident in operational efficiency, enhanced data accuracy, and improved accessibility to information. The study underscores the transformative impact of technology on the operational landscape, showcasing how its adoption has positively influenced the efficiency and effectiveness of business administration at CV Bangka Putra Persada.